2022
DOI: 10.1002/app.52705
|View full text |Cite
|
Sign up to set email alerts
|

Influence of MgO and ZnO as nano‐additives on the mechanical, microstructural and thermal performance of high‐density polyethylene

Abstract: Polymer nanocomposites have placed themselves in a highly favorable position in use in practical applications, with materials currently employed in technology related processes. This is because they have improved chemical, physical, morphological, structural, and mechanical properties compared to their polymer microcomposites counterparts or even neat polymer. In this study, two inorganic nanofillers, namely magnesium oxide nanoparticles (MgO NPs) and zinc oxide nanoparticles (ZnO NPs) were separately incorpor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 57 publications
(136 reference statements)
0
2
0
Order By: Relevance
“…The retention of HDPE's mechanical properties, especially the elongation at break, is ascribed to the enhanced intermolecular and intramolecular chain interactions within the HDPE matrix when combined with the DE/ZnO composite. Furthermore, it can be inferred that the addition of T700 to the test specimens in various proportions yields similar mechanical properties as observed in the HDPE/DE/ZnO composite samples [42][43][44].…”
Section: Characterizationmentioning
confidence: 60%
“…The retention of HDPE's mechanical properties, especially the elongation at break, is ascribed to the enhanced intermolecular and intramolecular chain interactions within the HDPE matrix when combined with the DE/ZnO composite. Furthermore, it can be inferred that the addition of T700 to the test specimens in various proportions yields similar mechanical properties as observed in the HDPE/DE/ZnO composite samples [42][43][44].…”
Section: Characterizationmentioning
confidence: 60%
“…But, introduction of ZnO fillers with a high content (50 wt%) can produce partial agglomeration of the inorganic particles in the resin matrix (Figure 2C), leading to abrupt decrease in the elongation at break of the HDPE/ZnO composites. As the tensile load increases, the polymer matrix elongates in the usual manner, while the rigid filler resists deformation, creating a frictional confinement between the filler and the polymer matrix, producing low elongation at fracture 45 …”
Section: Resultsmentioning
confidence: 99%
“…%. Mahmoud et al [ 53 ] found that when the content of nano-particles increased in the polymer with a uniform distribution, the crystalline regions increase, causing higher crystallinity in HDPE.…”
Section: Resultsmentioning
confidence: 99%